Discrete genetic boundaries of three Streblospio (Spionidae, Annelida) species and the status of S. shrubsolii - Mahon, A. R.; Mahon, H. K.; Dauer, D. M.; Halanych, K. M. (Marine Biology Research, 2009)
Spionid polychaetes are a dominant component of benthic assemblages in marine and estuarine habitats and are important in assessing ecological function and integrity. Ecological and biogeographic studies rely upon the ability to distinguish between morphologically similar species, as well as knowledge of evolutionary relationships between species. Unfortunately, differentiating between congeneric species of spionids can be challenging thereby potentially creating mistakes in scientific investigations. For example Streblospio contains three recognized species ( S. benedicti, S. shrubsolii, S. gynobranchiata) with few distinguishing morphological characters. Herein, we use similar to 500 bases of the mitochondrial cytochrome c oxidase subunit 1 gene (COI) to investigate the status of S. shrubsolii relative to other Streblospio. COI has previously been used to distinguish North American Streblospio benedicti and S. gynobranchiata. Results indicate all three Streblospio species are reciprocally monophyletic with S. shrubsolii basal to a well-supported S. benedicti/S. gynobranchiata clade.
World Polychaeta Database (WPolyD)